Decomposition behavior of yttria-stabilized zirconia and its effect on directed energy deposited Ti-based composite material. (10th June 2022) - Choi, Gwanghyo; Choi, Won Seok; Lee, Yoon Sun; Kim, Dahye; Sung, Ji Hyun; An, Seungjun; Oh, Chang-Seok; Hattal, Amine; Djemai, Madjid; Bacroix, Brigitte; Dirras, Guy; Choi, Pyuck-Pa
Highlights: The present study focuses on the rule of YSZ nanoparticles in the refined both α and β grains and increased strength of additively manufactured Ti-6Al-4 V (Ti64). The YSZ nanoparticles decomposed during the deposition process and led to the formation of Y2 O3 and some excess oxygen in the Ti64 matrix. The decrease in the sizes of the prior β grains could be attributed to the increasing amount of dissolved oxygen and yttrium, which promoted constitutional supercooling. The reduction in the size of the α grains could be ascribed to a shift of the onset of the β → α+β transformation to a higher temperature and shorter time with increasing concentration of dissolved oxygen. The contributions of the underlying strengthening mechanisms (α grain size, oxygen solid solution, Y2 O3 precipitate) for the as-deposited specimens were quantitatively determined. Abstract: We report on the microstructure and the strengthening mechanisms of additively manufactured parts fabricated by directed energy deposition of Ti-6Al-4V (Ti64) powders blended with yttria-stabilized zirconia (YSZ) nanoparticles. These specimens showed refined microstructures as compared to bare as-deposited Ti64, where the α and columnar prior β grain sizes decreased with increasing YSZ content. The YSZ nanoparticles decomposed during the deposition process and led to the formation of yttrium oxide and some excess oxygen in the Ti64 matrix. The decrease in the sizes of the prior β grains could be attributed to the increasing amount of dissolved oxygen and yttrium, which promoted constitutional supercooling. Furthermore, the reduction in the size of the α grains could be ascribed to a shift of the onset of the β → α+β transformation to a higher temperature and shorter time with increasing concentration of dissolved oxygen. Finally, the contributions of the underlying strengthening mechanisms for the as-deposited specimens were quantitatively determined. Graphical abstract: Image, graphical abstract